Implementation of a single-phase matrix converter induction motor drive - Sunter, Sedat; Aydogmus, Oemuer (Springer, 2008)
This paper presents an implementation of a single-phase matrix converter for a variable speed single-phase induction motor. The paper analyzes the characteristics of a single-phase ac-ac converter drive with particular emphasis on the harmonic content, input voltage utilization and variable speed performance of the motor. Both square and sinusoidal wave modulation signals in PWM generation have been used to demonstrate the effect of the modulating signal on the input voltage utilization and output harmonic content. Simulation and experimental results for an R-L and induction motor loads are presented. Promising results illustrate that a good performance of a single-phase induction motor fed by a matrix converter is achievable.
Keywords: single-phase matrix converter; single-phase induction motor